Canine Multicentric Lymphoma: Diagnostic, Treatment, and Prognostic Insights - Rocha, Michelle do Carmo Pereira [UNESP]; Araújo, Diana; Carvalho, Fátima; Vale, Nuno; Pazzini, Josiane Morais; Feliciano, Marcus Antônio Rossi; De Nardi, Andrigo Barboza [UNESP]; Amorim, Irina (MDPI, 2025)
Lymphoma accounts for 24% of all documented canine neoplasms and 85% of hematological malignancies, while multicentric lymphoma corresponds to 84% of all canine lymphomas. Canine lymphomas of B-cell origin account for 60% to 80% of lymphomas. Similar to humans, the histologic grade, architecture, as well as immunophenotype determination, are crucial. These lesions are the most prevalent spontaneous tumors in dogs and this species may be a valuable animal model for the study of human non-Hodgkin’s lymphoma. Therefore, it is important to investigate and assess therapeutic responses and to seek predictive and prognostic factors in order to allow for the development of an individualized and more effective therapy that increases survival. This review aims to describe current knowledge on the diagnosis, treatment, and prognostic factors of canine multicentric lymphoma.
Keywords: chemotherapy; comparative oncology; dog; immunotherapy; lymphoma